The Development of Pattern of Learning Network Making and Well-being Based on Buddhism in Chanthaburi Province - Titasatto, Phapalud Vejayun; Krongbun, Sirawat; Kotchai, Taworn; Sujitkittiwat, Phrakru; Suntornkemapinan, Phrakru (Journal of International Buddhist Studies, 2019)
Qualitative research has the objectives 1) to study the creation of a learning network and the health of the Mueang Phaniat community 2) to study the development of the area to be a learning source and to enhance the health of Buddhism 3) to study the promotion of learning and learning in accordance with the principles of Bhavana 4 and 4) to develop a model for creating a learning network and health in accordance with Buddhism Chantaburi province. This study uses research tools in documents, action research, in-depth interviews and focus groups. The researcher collected data from 8 key informants and 6 focus group participants. The results of the research were as follows: 1. The creation of faith by allowing the community to participate in network management such as systematic 2. There is a development of learning resources and health promotion under the promotion of the relationship between participatory networks such as joint thinking, doing and decision making. There are also new generation leaders. 3. Bhavana 4 is used as a guideline for enhancing the learning, health and quality of life of the community. The community agreed to the Wat Tongtua temple as a learning center for health and social development according to Buddhism.